“Said tree is a veritable nuisance”: Ottawa's Street Trees 1869-1939 - Dean, Joanna (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2005)
Street trees exist in an ambiguous space between built and natural environments, their status reflecting shifting attitudes towards the natural world. Their place was especially evident in debates over street trees in Ottawa between 1869 and 1939. In the late nineteenth century, homeowners were encouraged to plant trees, to bring esthetic order to the residential streetscape and to reduce miasma. But as they matured, the trees came into conflict with the rapidly expanding infrastructure of sidewalks, asphalt paving, and utility wires. The Ottawa Horticultural Society, led by Dominion Horticulturalist W. T. Macoun, urged city council to have them managed professionally. In response, during the 1920s and 1930s the city engaged in an extensive program of tree trimming and removal, targeting the American elm.